2011
DOI: 10.1111/j.1744-313x.2011.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning, genomic structure and mRNA expression pattern of porcine type I interferons receptor 2 gene

Abstract: Type I interferons (IFN) are important mediators of the host defence against viruses through binding to the cell surface receptors, among which the binding to type I IFN receptor 2 (IFNAR2) is the very first step initiating a complex signal transduction cascade. By using RT-PCR and 5' RACE approaches, we obtained porcine IFNAR2 cDNA, the nucleotide identity of its coding region is 57.53%, 67.45%, 74.07% and 74.63% to those of mouse, human, sheep and cattle, respectively; and the deduced protein of which shares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…6). This finding is in line with the previous study that porcine IFNAR2 is expressed at a higher level in the small intestine than in the large intestine (53). In contrast to the mainstream opinion that type III IFN-specific receptor IFNLR1 dominantly expresses in epithelia, we found that the transcriptional expression of type I IFN receptors (IFNAR1 and IFNAR2) was slightly higher than that of IFNLR1 in enteroids (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…6). This finding is in line with the previous study that porcine IFNAR2 is expressed at a higher level in the small intestine than in the large intestine (53). In contrast to the mainstream opinion that type III IFN-specific receptor IFNLR1 dominantly expresses in epithelia, we found that the transcriptional expression of type I IFN receptors (IFNAR1 and IFNAR2) was slightly higher than that of IFNLR1 in enteroids (Fig.…”
Section: Discussionsupporting
confidence: 93%